2020
DOI: 10.2174/1874149502014010289
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cassava Starch on the Durability Characteristics of Concrete

Abstract: Background: Concrete is a common material used in the construction of marine structures, such as bridges, water treatment plants, jetties, etc. The use of concrete in these environment exposes it to attack from chemicals like sulphates, chlorides and alkaline, thereby causing it to deteriorate, and unable to perform satisfactorily within its service life. Hence, the need to investigate the durability properties of concrete has become necessary especially when admixtures are used to modify s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
(3 reference statements)
2
9
0
Order By: Relevance
“…Because of its viscosity characteristics and thickening ability, starch in concrete lowers its workability. The results were in line with the findings of Okafor (2010) [36], and Xavier (2020) [59], but disagreed with Agbi & Uguru (2021) [60], and Oni et al (2020) [61].…”
Section: Fresh Properties and Slumpsupporting
confidence: 81%
See 1 more Smart Citation
“…Because of its viscosity characteristics and thickening ability, starch in concrete lowers its workability. The results were in line with the findings of Okafor (2010) [36], and Xavier (2020) [59], but disagreed with Agbi & Uguru (2021) [60], and Oni et al (2020) [61].…”
Section: Fresh Properties and Slumpsupporting
confidence: 81%
“…Age-related gains in strength have been seen, for instance, by Okafor (2010) [36]. Similar findings were found by Ikoko et al, 2021 [41], Xavier (2020) [59], Kone et al (2022) [34], and Oluwabusayo Oni et al, (2020) [25]. Since it can make concrete stronger when it's pressed, cassava flour could be thought of as a green material additive.…”
Section: Compressive Strength (Cs)supporting
confidence: 60%
“…The relative strength is reported to be 711.5 kg/cm2 in addition to the brick being more environmentally responsive. Elsewhere, experimental trials of cassava starch modified concrete confirmed improved compressive, split tensile, flexural and elastic modulus of concrete at an optimum of 0.8% as well increased setting time and durability, with potential application in retarding admixtures [40,41].…”
Section: Other Applications Of Cassavamentioning
confidence: 99%
“…This type of starch contains two categories of macromolecules, called linear amylose and branched amylopectin, which consist of glucose chains [140]. Branched amylopectin accounts for 83% of the carbohydrate content present in cassava roots, while linear amylose occurs in a much smaller percentage, approximately 17% [112].…”
mentioning
confidence: 99%
“…This glucose chain (amylose and amylopectin) that makes up cassava starch has been shown to give the cement mix greater strength and flexibility compared to mortars lacking this substance [146,147]. It also improves the durability properties of concrete when exposed to chloride-rich, sulphate-rich, or alkaline environments [140].…”
mentioning
confidence: 99%